Atomized flux for jet valve dispensers

By developing a mixed welding agent combination containing fluoride-based welding agent and adding an appropriate amount of thickener and other ingredients, the problem of difficult to develop high-welding performance welding agent suitable for printing in the prior art is solved, and an efficient and high-quality welding and printing process is achieved.

JP2025513756APending Publication Date: 2025-04-30HONEYWELL INTERNATIONAL INC
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
JP2024558011
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-04-03
Filing Date
2023-04-06
Publication Date
2025-04-30

AI Technical Summary

Technical Problem

The difficulty in developing fluoride-based soldering agents suitable for printing with high welding properties is a challenge, especially to adapt to the physical properties of the printing system while maintaining high welding properties.

Method used

A mixed welding agent combination containing a fluoride-based welding agent was developed to form a consistency characteristic suitable for contactless inkjet printing systems by adding an appropriate amount of thickening agent, carrier, dispersing agent, wetting agent, antifoaming agent, reducing agent and biofungicide.

Benefits of technology

It achieves a balance between high welding performance and high printing adaptability, and can adapt to the physical properties of the printing system while maintaining high welding performance, improving the efficiency and quality of the welding process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025513756000001_ABST
    Figure 2025513756000001_ABST
Patent Text Reader

Abstract

A flux paste composition comprising one or more fluoroaluminate-based fluxing agents, one or more thickeners, a carrier, a dispersant, a wetting agent, a defoamer, a moderator, and a biocide. The flux paste composition may be blended with one or more rheology additives selected based on printing of the blended flux composition by a non-contact inkjet printing system.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to U.S. Patent Application No. 18 / 130,025, filed April 3, 2023, which claims the benefit under 35 U.S.C. §119(E) of U.S. Provisional Application No. 63 / 329,592, filed April 11, 2022, both of which are incorporated by reference herein in their entireties.

[0002] FIELD OF THEINVENTION The present disclosure relates generally to flux compositions that are printable by inkjet printing systems. [Background technology]

[0003] Brazing operations used in certain manufacturing operations, such as the manufacture of heat exchangers, have traditionally been performed in vacuum furnaces. More recently, a brazing technique known as "controlled atmosphere brazing (ustCAB)" has been accepted by the automotive industry to make brazed aluminum heat exchangers. Exemplary end uses for CAB brazed aluminum heat exchangers include radiators, condensers, evaporators, heater cores, charge air coolers, and intercoolers.

[0004] CAB brazing is preferred over vacuum furnace brazing due to increased production yields, reduced furnace maintenance requirements, increased brazing process robustness, and lower capital costs of the equipment utilized.

[0005] In the CAB process, fluxing or fluxing agents are applied to the surfaces of pre-assembled components to be joined. The fluxing agents are used to dissociate or dissolve and displace the aluminum oxide layer that naturally forms on the aluminum alloy surfaces. The fluxing agents are also used to prevent reformation of the aluminum oxide layer during brazing and to enhance the flow of the brazing alloy. Exemplary fluxing agents include alkali or alkaline earth metal fluorides or chlorides.

[0006] Fluoride-based fluxes are generally preferred for brazing aluminum or aluminum alloys because they are inert or non-corrosive as is aluminum and its alloys, are substantially water-insoluble after brazing, and are commonly used by the automotive industry in the manufacture of aluminum and aluminum alloy heat exchangers.

[0007] Heat exchanger and engine oil cooler components made of aluminum are conventionally extensively coated with flux paint and brazed, however, a small percentage of the flux contained in the flux paint is absorbed into the solder and found as an undesirable residue in the liquid cooling medium after soldering.

[0008] More recently, flux paints have been printed onto such components. However, printing of the flux has proven difficult due to the rheological profile and / or physical properties of the flux formulation. There is a need for fluxing agent compositions that provide physical properties that can be compatible with printing systems while maintaining brazing performance. Summary of the Invention

[0009] The present disclosure provides flux paste formulations including fluoride-based fluxing agents that, when combined with one or more additional additives, form blended flux compositions printable by non-contact inkjet printing systems. The blended flux compositions exhibit high printability while maintaining high brazing performance.

[0010] In one embodiment, the present disclosure provides a flux paste composition comprising one or more fluoroaluminate-based fluxing agents, one or more thickening agents, a carrier, a dispersant, a wetting agent, a defoamer, a moderator, and a biocide.

[0011] In another embodiment, the present disclosure provides a blended flux composition comprising a micronized flux paste comprising one or more fluoroaluminate fluxing agents and one or more rheological additives selected based on printing of the blended flux composition with a non-contact inkjet printing system.

[0012] In a further embodiment, the present disclosure provides a method of printing a blended flux formulation comprising: preparing a flux concentrate comprising one or more fluoroaluminate fluxing agents, one or more thickeners, a carrier, a dispersant, a wetting agent, a defoamer, a moderator, and a biocide; micronizing the flux concentrate to form a micronized flux paste; adding one or more rheology additives to the micronized flux paste to form a blended flux formulation; and inkjet printing the blended flux formulation. [Brief description of the drawings]

[0013] [Figure 1] Illustrates an embodiment of printed dot lines of the compositions of Examples B, C, D, E, F, G, and K performed with a Nordson jet print head. [Diagram 2]1 illustrates an embodiment of a Nordson jet printing nozzle that demonstrates the viscosity limits of a jet flux formulation. [Diagram 3] Illustrates an embodiment of a Nordson jet printing nozzle with splashing and clogging due to improper consistency of printing paste. [Figure 4] 1 illustrates embodiments of printed dot structures of various jet flux formulations resulting from the performance testing described in the Examples section of this disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] I. Preparation The present invention relates to a flux composition, including, but not limited to, any combination of micronized blended flux pastes including fluoride-based fluxes, shear thinning agents, low VOC solvents, and polymeric dispersants. The flux composition can be used in various printing applications, such as inkjet printing. For example, the flux composition can be used in a non-contact high frequency inkjet printing process, where the flux composition is applied in a pattern to join components of dissimilar or similar metal (e.g., aluminum) alloy parts in a brazing process.

[0015] Precision application of the flux formulation can be achieved by printing with an inkjet-printed fluid dispensing system. A conventional continuous inkjet (CIJ) printing system includes a syringe barrel and a dispensing tip, among other suitable components. Conventional CIJ printing tips are relatively small in diameter, e.g., about 1.0-2.0 mm, although some tip diameters can be larger or smaller. Conventional inkjet-printed fluid dispensing systems print the fluid in a continuous stream, allowing for the rapid and precise application of a variety of patterns of flux compositions. These types of systems are commonly used throughout industry, including in tube folding machines.

[0016] Non-contact inkjet printing, also known as jetting, is an improvement over conventional CIJ printing systems. One example of non-contact inkjet printing is drop-on-demand (DOD) inkjet printing. DOD printing technology is a non-contact inkjet printing fluid system that ejects fluid one drop at a time from a small diameter jet nozzle. The nozzle diameter of a DOD system can be smaller than a conventional inkjet fluid delivery system tip, e.g., about 0.1-0.8 mm (compared to, e.g., over 1 mm for conventional inkjet printing devices). As such, the maximum particle size of the flux paste ingredients is an important characteristic for DOD applications, since DOD printing systems require smaller particle diameters than those of conventional inkjet tips (e.g., to avoid clogging of the DOD fluid delivery system).

[0017] DOD type inkjet systems can print the flux formulation by a variety of means, including both mechanical and electrical means. In the case of mechanical means, the fluid can be forced out of the nozzle as individual droplets by acoustic waves or volumetric expansion. In the case of electrical means, piezoelectric DOD inkjet printers can be utilized, where a voltage is applied to a piezoelectric transducer coupled to the printing nozzle, causing the shape of the piezoelectric material to change and generate pressure pulses in the fluid that force droplets of fluid out of the nozzle. In both of these cases, droplets of fluid are non-contact-ejected (e.g., without the need for any contact between the nozzle and the substrate) from the printing nozzle at high frequencies, and as many as eight droplets can be ejected to create weakly cohesive / combined droplets of fluid on the substrate (e.g., allowing for greater flexibility in droplet size than traditional approaches). Additionally, due to the non-contact jetting nature of the printing, droplets are fired (e.g., jetted) from the printing nozzle rather than requiring contact with the substrate as in traditional CIJ printing systems, so printing can be accomplished in any type of horizontal and vertical orientation, such as via a print head mounted on a robotic arm.

[0018] Such DOD type fluid dispensing systems allow for a great deal of flexibility when printing flux formulations onto various build parts. Furthermore, DOD systems allow manufacturers to dispense numerous types of flux at relatively high speeds and with high precision. As such, non-contact inkjet printing such as DOD type printing can reduce waste generated during the brazing process (e.g., via dispensing only the required amount of flux), avoid unnecessary rework and / or product rejection (e.g., via improved precision of the printing process), and thus provide higher throughput compared to other brazing approaches (e.g., via the rapid application capabilities of inkjet printing systems in general, and DOD type printing systems in particular).

[0019] Although the speed of non-contact inkjet printing systems has increased, this increased speed has led to some drawbacks. High frequency jet valve systems can fire droplets at frequencies above 250 Hz. However, high frequency non-contact printing systems often require thickeners to increase the flux paste viscosity. For example, flux formulations for non-contact inkjet printing exhibit high viscosities of up to 5000-15.0000 mPas. In this case, glycols are often used as thickening additives, which in some cases can account for up to 45% by weight of the flux paste. High concentrations of thickeners impair the effectiveness of the paste by creating a poor quality suspension surface that does not dry easily on the substrate (e.g., by including too much thickener relative to the flux). Furthermore, conventional flux formulations often have a wide particle size distribution, which can include flux particles with large diameters. As a result of these characteristics, conventional flux formulations for tip dispensing and / or formulations for paints exhibit problems when pumping and passing through fine tubes. These flux formulations can therefore lead to clogging of the nozzles of the inkjet head.

[0020] Additionally, higher viscosity flux pastes also require the use of more energy when printing. In this case, higher energy and higher frequency jet firing generates excess heat at the jet valve head. To counter this localized buildup of heat, the print head may be cooled using a circulating water system. Thus, although conventional jet printing systems may enable precise application of flux paste for brazing processes, their shortcomings present a major obstacle in increasing the speed of jet printing of such formulations.

[0021] The present invention relates to an improved flux formulation that can be combined with one or more additional additives to form an overall jet flux formulation. The jet flux formulation can be used in a variety of inkjet type printing applications, including non-contact inkjet printing, specifically DOD type inkjet printing applications. The jet flux formulation has a relatively high viscosity of 2000-3000 mPas, allowing for high speed printing of the flux by conventional inkjet printing, non-contact ink jetting, and / or high frequency non-contact ink jetting (e.g., high frequency DOD systems). For example, a preferred viscosity range for the jet flux formulation is 2000-4000 mpas. Higher viscosities can lead to non-uniform droplet formation at the print head and undesirable filament formation. Too low a viscosity can lead to droplet formation at the print head, leading to increased splatter at the nozzle and the formation of spray mist. The jet flux formulation can be substantially free of product-impairing thickeners, such as glycols. The improved flux formulation may also contain a relatively high percentage of fluxing agent, allowing for fast printing of small dots of the flux formulation while achieving high brazing performance. The flux paste is a semi-finished product and may also contain 47% flux, of which 96% is potassium-based (K) flux and 4% is cesium-based (Cs) flux. The percentage of Cs flux is even sufficient for brazing aluminum alloys containing up to 0.6% magnesium. Since the Cs and K fluxes can be added in high proportions, the paste can be tailored according to the application. Since the Cs flux is expensive, the amount used can be less than the K flux. A flux concentration of 20-40% absolute by weight is sufficient to produce reliable solder joints. However, since the application amount in the printing process is relatively small, the flux concentration of the formulation can be much higher than 20-40% absolute by weight. The viscosity of the semi-finished paste increases sharply with increasing solids content, so 40-50% by weight may be preferred for processability reasons.

[0022] The improved flux formulation may include any combination of one or more fluxing agents, shear thinning agents, carriers, dispersants, wetting agents, defoamers, moderators, and / or biocides. In some cases, the flux formulation may be in the form of a paste. Therefore, hereinafter, the improved flux formulation is referred to as a flux paste formulation.

[0023] The fluxing agent of the flux paste formulation may be selected from any number of fluoride-based fluxes suitable for brazing applications. For example, the fluxing agent may be a tetrafluoroaluminate-based fluxing agent, which may be selected from any suitable tetrafluoroaluminate-based compound. Specifically, the fluxing agent may be any of potassium aluminum fluoride (KAlF4), cesium aluminum fluoride (AlCsF4), aluminum fluoride (AIF3), cesium fluoride (CsF), rubidium fluoride (RbF), lithium fluoride (LiF), sodium fluoride (NaF), and calcium fluoride (CaF2); potassium fluoroaluminates, such as potassium pentafluoroaluminate (K2AIF5, K2AIF5 H2O) and potassium hexafluoroaluminate (K3AIF6), or combinations thereof. Examples of such fluxes are described in GB 1438955(A), U.S. Patent Nos. 4,428,920, 3,951,328, 5,318,764, and 4,579,605. Aluminum oxyfluorides such as AI2F4O and AIFO may also be used. Aluminum hydroxyfluorides such as AIF2(OH), AIF2(OH)-H2O, and AIF(OH)2 may also be used. Fluoroborates such as potassium tetrafluoroborate (KBF4) and sodium tetrafluoroborate (NaBF4) may also be used. Examples of such fluxes are described in GB 899171(A), GB 1007039(A), and U.S. Patent No. 4,235,649. Also suitable are fluorozincates such as potassium trifluorozincate (KZnF3), potassium tetrafluorozincate (K2ZnF4), cesium trifluorozincate (CsZnF3), and cesium tetrafluorozincate (Cs2ZnF4). Examples of such fluxes are described in DE 19913111(A) and WO 9948641(A).Alkali metal fluorosilicates such as cesium hexafluorosilicate (Cs2SiF6), potassium hexafluorosilicate (K2SiF6), lithium hexafluorosilicate (Si2SiF6), rubidium hexafluorosilicate (Rb2SiF6), sodium hexafluorosilicate (Na2SiF6), and ammonium hexafluorosilicate ((NH4)2SiF6) may be used. Examples of such fluxes are described in U.S. Pat. No. 5,785,770, German Patent No. 19636897(A), U.S. Pat. Nos. 5,985,233, 6,019,856(A), 5980650, and WO 98 / 10887(A). Alkali bimetal fluorosilicates such as potassium cesium hexafluorosilicate (KCsSiF6), lithium cesium hexafluorosilicate (LiCsSiF6), rubidium cesium hexafluorosilicate (RbCsSiF6), rubidium potassium hexafluorosilicate (RbKSiF6), and ammonium cesium hexafluorosilicate (NH4CsSiF6) may be used. Alkali metal bifluorosilicates (also called alkali metal hydrofluorosilicates) such as cesium hydrofluorosilicate (CsHSiF6), potassium hydrofluorosilicate (KHSiF6), lithium hydrofluorosilicate (LiHSiF6), and ammonium hydrofluorosilicate (NH4HSiF6) may be used. Also suitable are cesium fluoride (CsF), cesium hexafluoroaluminate (Cs3AIF6), cesium tetrafluoroaluminate (CsAIF4H2O), and cesium pentafluoroaluminate (CsAIF5, CsAIF5.H2O), and other cesium fluoroaluminate complexes. Examples of such fluxes are described in U.S. Patent Nos. 4,670,067, 5,171,377, 5,806,752, 5,771,962, and 4,655,385. So-called superfluid fluxes can be used as well.

[0024] As described in connection with U.S. Patent Application Nos. 16 / 000,176 and 16 / 000,178, which are expressly incorporated herein, fluoride-based fluxing agents, and in particular KAlF4, exhibit advantageous properties when used as fluxing agents in brazing processes. In this case, KAlf4 can be used alone or in combination with AlCsF4 as a fluxing agent in a flux paste formulation. For example, if a flux paste formulation includes both KAlf4 and AlCsF4 fluxing agents, KAlf4 can be the majority fluxing agent, making up 95% or more of the combined fluxing agents, and AlCsF4 can be the minor component, making up 5% or less of the combined fluxing agents. In either of these cases, the fluxing agent can comprise about 40-50% by weight of the overall flux paste formulation composition. By mixing KAlF4 and CsAlF4, any melting point between 435°C and 560°C can be obtained. Typically, the flux or flux mixture melts at 20-50°C below the temperature of the soldering components. If the flux melts at a lower (e.g., too low) temperature, it may evaporate before the solder melts and not have its effect. In this case, it may be desirable for the flux paste formulation to contain 1-2% cesium flux. This amount of cesium flux may be sufficient to improve the adhesion of the flux application, lowering the melting temperature by 5-10°C, and / or brazing aluminum alloys containing magnesium. Alternatively, some flux paste formulations (e.g., used in repair pastes) contain 2-6% Cs flux to melt thicker oxide layers fast enough. A higher percentage of cesium-containing flux is used to join aluminum alloys with ZnAl solder at lower temperatures.

[0025] The flux paste formulation may also include other ingredients such as thickeners. The particular thickener utilized may be selected based on the effect it has on the physical properties of the flux paste formulation, for example, on the overall rheological profile of the flux paste formulation. For example, the thickener may be selected based on the shear thinning effect it has on the rheological profile of the flux paste formulation, such that the overall jet flux formulation is printable by a high frequency DOD inkjet printing system. The shear thinning thickener may be selected from any of a variety of suitable shear thinning thickeners, including cellulose ether-based thickeners (e.g., hydroxyethyl cellulose (HCE thickeners)), polysaccharide (PSC)-based thickeners, and / or acrylate-based thickeners. For example, the shear thinning thickener may be a PSC thickener, such as diutan gum, guar, xanthan, cellulose, carob, and acacia. Additionally or alternatively, sugars may be used, including carrageenan, pullulan, konjac, and alginates, sometimes referred to as hydrocolloids.

[0026] The shear thinning thickener may comprise less than 1 wt.% of the composition of the overall flux paste formulation. For example, the shear thinning agent may comprise 0.01 wt.% to 0.5 wt.%, 0.01 wt.% to 0.1 wt.%, and / or in preferred embodiments, 0.03 wt.% of the overall flux paste formulation, or any other value encompassed by these ranges. Additionally or alternatively, ACH thickeners may also be used, and when used in combination, a more complex and broader rheological profile of the paste is observed.

[0027] The flux paste formulation may also include a carrier, such as water, glycols, and alcohols. In some cases, solvents with high boiling points and low hazard risk, such as propylene glycol, hexylene glycol, propylene carbonate, or methyl methoxymethyl butanol, may be used. In some embodiments, the carrier may comprise 0% to 58% by weight, or more preferably 0% to 35% by weight, of the composition of the flux paste formulation, or any other value encompassed by these ranges.

[0028] The flux paste formulation may also include a dispersant. The dispersant may be a polymer (e.g., a polymeric dispersant) that acts to separate individual fluxing agent particles by steric stabilization. For example, the polymeric dispersant may be Disperbyk 190, Zetasperse 1600, acrylates, polyurethanes, polyalkoxylates, fatty acids, and phosphoric acid derivatives. The dispersing additive leads to a uniform distribution of fine and solid particles in the liquid medium, ensuring the long-term stability of such systems. The additive stabilizes pigments (e.g., inorganic and organic pigments, as well as inorganic salts) and fillers by steric or ionic effects. Wetting and dispersing additives combine both active ingredients in one product, e.g., Zetasperse 1600 (i.e., the active ingredient has a wetting and stabilizing effect at the same time). Standard products are sufficient for the polar surfaces of inorganic pigments and fillers, while polymeric additive solutions are used for highly charged fluoroaluminates and their acidic surfaces to achieve sufficient wetting and stabilization in the system. The dispersant may comprise the composition of the flux paste formulation from about 0.04% to 2.0% by weight, 0.04% to 0.8% by weight, 0.08% to 0.4% by weight, or any other value encompassed by these ranges.

[0029] The flux paste formulation may also include a wetting agent. The wetting agent may also exert a rheological effect on the composition of the flux paste formulation, such as exhibiting hydrophobic association with other components of the flux paste formulation, thus competing with the thickening effect at the surface of the dispersed flux particles. This may produce a deflocculating effect on the flux paste formulation. Examples of wetting agents include ZetaSperse® 1600, BASF: Plurafac® LF grades, i.e., Plurafac LF120, 220, 403, 700, 901, 1430; Lutensol® TO, AO, XL, ON grades; Sasol grades, i.e., Marlox®, Marlipal®; Elementis, i.e., Servoxyl; Allnex: Additol grades; and Julius Hoesch: Berol grades. The wetting agent may comprise 0.01% to 2% by weight of the composition of the flux paste formulation.

[0030] The flux paste formulation may also include a defoaming agent (e.g., defoamer), such as Surfynol 104 50GP; EVONIK: Surfynol grades, i.e., Surfynol 104, Surfynol DF110, Surfynol AD01; BASF: Degressal, Pluriol, FoamStar®, Foamaster®; BYK: Byk-1711, Byk-011, and Byk-016 silicon-free polymeric defoamers. The defoaming agent may comprise less than 1 wt. % of the composition of the flux paste formulation.

[0031] The flux paste formulation can also include a moderator (e.g., a moderator). The moderator can be selected from any one or combination of polyethylene glycol sorbitan monolaurate (TWEEN® 20), polyoxyethylene sorbitan monopalmitate (TWEEN® 40), POE(20) sorbitan monooleate (TWEEN® 80), ethylene glycols such as EG ethylene glycol, DEG diethylene glycol, TEG triethylene glycol, propylene glycols such as PG, DPG, TPG, polypropylene glycols such as PPG400, PPG2000, and / or other polymers such as PE-PG copolymers, PLA-PEG copolymers, AC-PEG, 4-arm PEG, 8-arm PEG, hyperbranched PEG dendrimers, etc. For example, the moderator can be polyethylene glycol PEG20000. PEG is a suitable retarding agent because it facilitates atomization of the flux crystals and forms a lubricant film around the crystals when the agent melts during grinding, thus minimizing sliding friction. PEG also inhibits the contact of highly charged flux crystals in the settled state and facilitates redispersion of the paste after long-term storage. As a further example, the retarding agent may be selected from any one of TWEEN 20, 40, 80, PEG 400, PEG 1000, PEG 10.000, PEG copolymer, 4-arm PEG, 8-arm PEG, hyperbranched PEG dendrimer. The addition of the uncharged surfactant TWEEN above its critical micelle concentration (CMC) inhibited adhesion between uncoated particles. However, the degree of improvement in adhesion inhibition induced by this surfactant probably cannot exceed the quality of adhesion prevention we achieved by PEGylation. In any of these cases, the moderator may comprise 0.1% to 5% by weight, 0.1% to 3% by weight, 0.5% to 1% by weight, or any other value encompassed by these ranges of the composition of the flux paste formulation.

[0032] The flux paste formulation may also include a biocide such as 2-phenoxyethanol; Thor: Acticide BX-H (BIT), 14, B20; Lanxess: Preventol grades, DP25, DP18, BIT; BASF: Protectol GA24, GA25; Clariant: Nipacide BIT 10A; and BASF: Protectol PE. The biocide may comprise 0.01% to 5% by weight, 0.01% to 2% by weight, 0.1% to 0.5% by weight, or any other value encompassed by these ranges of the composition of the flux paste formulation.

[0033] As explained above, non-contact inkjet printing systems may utilize small diameter nozzles (e.g., 0.8-1.0 mm diameter). Therefore, it is necessary for the flux paste formulation to include particles having a diameter slightly or substantially smaller than the diameter of the printing nozzle so that the particles do not clog the nozzle during jetting.

[0034] Particle micronization is one method of reducing particle size to acceptable diameters. Micronization involves mechanical and / or high shear action to reduce the diameter of the particles to diameters in the micron (e.g., μm) range. For example, particles may be micronized to diameters of 100 μm to 1 μm, preferably 10 μm to 1 μm, more preferably 5 μm to 1 μm. Particle micronization is determined based on the measured average particle size distribution (e.g., D5, D50, D95, etc.) of the particles of the flux paste as determined by laser diffraction based on Mie scattering using a HORIBA LA-920.

[0035] Conventional methods of particle micronization include mechanically milling (e.g., dry grinding) the flux paste, sieving out oversized particles, and re-milling the larger particles. The use of dry grinding in the sub-sieve range of 625 mesh (20 microns) to 2500 mesh (5 microns) has proven impractical, and therefore conventional milling processes can be considered time consuming, expensive, and ineffective for reducing the size of flux paste formulations for jetting processes.

[0036] The formulation begins with the preparation of a flux concentrate (e.g., Jet Flux 2805-50Cs) to produce a micronized flux. Wetting agents, defoamers, and dispersants can be added before grinding the flux mixture in the selected composition to obtain a stable dispersion after wet-milling the flux. In this step, additives that are stable to grinding and heat are utilized since high local shear forces and high temperatures occur in the grinding media during the grinding process. For this reason, aqueous dispersions and various thickeners, such as those present in acrylate binders, can be added after the grinding process. Stabilization of the highly loaded flux paste is achieved by adding polymeric dispersants and polyethylene glycols that can lower the friction of the flux particles.

[0037] For micronization, a FRYMA MS-18 media mill 10HP was used. The annular gap bead mill transfers 4 times more energy to the product than a conventional agitator mill, improving particle size, but generating some heat. A standard feature of the CoBall® mill is an efficient cooling circuit with a large surface area that effectively removes unwanted heat. However, high shear forces degrade the rheology control agent and localized heat initiates agglomeration of the binder. To avoid these problems, additives are added to the milled material after milling and incorporated by a dissolver. With a fill ratio of 45-50%, the paste reaches a viscosity of about 11000mpas. Higher fill ratios may be possible, but the pumpability of the paste decreases, adversely affecting processability.

[0038] The use of a jet mill has been found to mill (i.e., atomize) flux paste material to single digit micron particle sizes in a single pass, increasing yield and operational efficiency. In this atomization method, the mill injects high velocity compressed air into a chamber where a speed controlled feeder adds the starting materials. As the particles enter the air stream, they are accelerated and collide at high velocities with each other and with the walls of the mill chamber. Particle size reduction occurs through a combination of collision and friction. Impact occurs due to collisions between the rapidly moving particles and between the particles and the walls of the mill chamber. Friction occurs at the particle surfaces as the particles move rapidly relative to each other, resulting in shear forces that can destroy the particles.

[0039] Beneficially, micronized flux pastes exhibit increased surface area over conventionally milled particles. Milling the material from 30 mesh (595 microns) to 2,500 mesh (5 microns) results in 1,643,000 times more particles and approximately 118 times more surface area. This allows for faster chemical reaction times and improved melting reactions of the flux paste. Thus, the composition of the flux paste formulation can be based on the ability to mill the flux paste via jet milling.

[0040] When applied via non-contact inkjet printing, stability of the micronized flux paste is an important requirement. It is desirable that no clumping, settling, or syneresis occur during storage. Thus, the paste should contain as high a practical proportion of fluxing agent (e.g., high weight percent) as possible and may contain minimal amounts of other ingredients. Preferably, the paste should be easy to handle (i.e., be able to flow or be pumped) and retain moisture (e.g., do not dry out easily).

[0041] Thus, the base flux paste formulation may be combined with one or more additional additives to form a blended flux formulation (hereafter referred to as the jet flux formulation). Additives may be included in the base flux paste formulation to target advantageous physical properties, including rheological profile. For example, to print the jet flux formulation while maintaining a target viscosity at high shear rates during printing, the addition of wetting and dispersing additives may reduce the viscosity of the flux composition and deflocculate the particles. It may also be advantageous to add polymeric additives, such as polymeric binders, to the flux paste composition. The additives are preferably compatible with the binders used in the flux formulation. Thus, the flux paste formulation may be combined with any combination of additional thickeners, dispersants, and / or carriers to target advantageous rheological profile and / or physical property effects thereon of the final jet flux formulation.

[0042] For example, when forming a jet flux formulation, the flux paste formulation may be combined with one or more additional thickeners. One example of an additional thickener includes a polysaccharide-based (PSC) thickener, such as a 1% aqueous solution of KelcoVIS DG (diutan gum). In some cases, the PSC thickener may act as a structural thickener and / or a shear thinning agent. The PSC thickener may comprise 1% to 12% by weight, 2% to 10% by weight, 3% to 6% by weight, or any other value encompassed by these ranges, of the composition of the jet flux formulation.

[0043] Another example of an additional thickener includes an acrylate-based thickener (e.g., an alkali swellable emulsion (ASE)). In some cases, the acrylate-based thickener may act as a structural thickener and may be considered an organic binder. In these cases, the acrylate thickener / organic binder may be Accusol 820, Arkema Group: Rheosolve™ T633, 635, 637; Ashland: Jaypol™ AT4; Dow Chemical: Acusol™ 820; Lubrizol: Carbopol™ EZ grades; BASF: Aethoxal™ TTN, TTA, other grades; and Elementis: RHEOLATE™ HX6008. The acrylate thickener / organic binder may comprise from 0% to 15% by weight, from 0.5% to 10% by weight, from 2% to 6% by weight, or any value encompassed by these ranges, of the composition of the jet flux formulation.

[0044] Another example of a thickener is a cellulose ether thickener, such as a hydroxyethyl cellulose (HEC) thickener or a hydroxypropyl cellulose (HPC) thickener. Specifically, HEC cellulose ether thickeners are highly soluble in water. Solutions containing HEC thickeners are clear and smooth, and visually gel-free. The solutions are non-Newtonian, as the viscosity changes with shear rate. HPC has a wide range of polar organic liquid solubility and provides clear solutions at ambient and elevated temperatures. Generally, the more polar the liquid, the better the solution. Methanol and ethanol, propylene glycol, and dioxane are suitable organic solvents for all types of HPC. The cellulose ether thickener may comprise 1% to 12%, 2% to 10%, or 3% to 6% by weight of the composition of the jet flux formulation, or any value encompassed over such ranges.

[0045] The final example of additional thickeners includes associative thickeners such as polyurethane (PU) thickeners. PU thickeners can be used to increase the viscosity of jet flux formulations in the high shear range. For example, PU thickeners can be hydrophobically modified ethoxylated urethane (e.g., HEUR) copolymers such as TegoRheo8510, Rheobyk7610, Acusol880 (DOW), TegoVisco Plus (Evonik), Tafigel PUR (Munzing), Rheovis PU (BASF), Schwegopur (Schwegmann), Rheobyk-T1000VF, T1010VF (BYK), and Rheobyk-L1400VF. The PU-based thickener may comprise 0.1 wt.% to 10.0 wt.%, 0.1 wt.% to 5.0 wt.%, or 0.5 to 2.0 wt.% of the composition of the jet flux formulation, or any value encompassed by such ranges.

[0046] The flux paste formulations may also be combined with one or more dispersing agents when forming the jet flux formulation. Dispersing additives lead to uniform distribution of fine and solid particles in the liquid medium, providing long-term stability of such systems. The additives stabilize pigments (inorganic and organic pigments, as well as inorganic salts) and fillers by steric or ionic effects. Wetting and dispersing additives combine both active ingredients in one product, e.g. Zetasperse 1600 (i.e., the active ingredients have wetting and stabilizing effects simultaneously). To achieve sufficient wetting and stabilization in the system, polymeric additive solutions are used for highly charged fluoroaluminates and their acidic surfaces. Commercially, there are different technologies available, such as acrylates, polyurethanes, polyalkoxylates, fatty acids, and phosphoric acid derivatives. For example, polymeric acrylate copolymers may be used, as they neutralize the surface charge, act by steric stabilization, and are easily thermally degraded. These dispersing agents may be polymers (e.g., polymeric dispersing agents) that act to separate the individual fluxing agent particles by steric stabilization. The dispersant may in particular be a polymeric dispersant such as Disperbyk 184, Disperbyk 190, DISPERBYK-2015 - VOC-free acrylic copolymer. It is very suitable for aqueous pigment concentrates and is based on CPT (controlled polymerization technology). This technology allows for a precisely defined molecular weight distribution, which allows for the application of many different binder systems. Disperbyk 184: High molecular weight polyurethane dispersant. Additionally or alternatively, Byk: Disperbyk® grades; Bykjet grades; BASF: Dispex Ultra® grades; Evonik: Zetasperse® grades; Newos-gmbh: Newo Tec®; Munzing Chemie: Edaplan® may be used. The polymeric dispersant may comprise 0.1% to 5% by weight, 0.1% to 2% by weight, 0.2 to 0.8% by weight of the composition of the jet flux formulation, or any value encompassed by such ranges.

[0047] The flux paste formulation may also be combined with one or more carriers when forming the jet flux formulation. The carrier may specifically be water, glycol, alcohol, and high boiling point, low hazard solvents such as propylene glycol, hexylene glycol, propylene carbonate, methyl methoxybutanol. The carrier may comprise 5% to 70% by weight, 10% to 30% by weight, 15% to 25% by weight of the composition of the jet flux formulation, or any value encompassed by such ranges.

[0048] Surprisingly, it has been found that the combination of structural thickeners and PU thickeners is particularly suitable for jet flux formulations containing potassium tetrafluoroaluminate flux. Without being bound by theory, this is believed to be due to the low number of wetting agents and the high amount of flux used in the flux formulation. Therefore, jet flux formulations containing a thickener acting as a shear thinning agent selected from one of the above-mentioned PSC, HCE, and HEUR thickeners have been shown to be particularly advantageous.

[0049] In either of these cases, additional additives are frequently added to the flux formulation during the final stage, and these wetting and dispersing additives may be added to the mill base and ground with the flux paste.

[0050] II. Formulation testing Figures 1, 2, 3 and 4 illustrate printing tests performed on various formulations corresponding to the specific blending choices described in relation to Section III. Examples are provided below.

[0051] The printing performance of the flux paste formulation was found to be dependent on the viscosity of the formulation which is influenced by the balance of ingredients in the formulation. Viscosity is exponentially reduced by thinning with water. Addition of 20% water can produce a target range of 2000-4000 mPas for the viscosity of the micronized paste. As shown in Table 14 below in relation to Section III: Printing performance of Jet Flux Paste Formulations, the addition of structural thickener PSC only slightly increases the viscosity but reduces the frictional drag of the flux particles while maintaining the environment and also prevents settling and also prevents particle agglomeration like PEG.

[0052] In Figure 1, the printed dot lines immediately show that without the PSC (e.g., Tests 110, 113), the jet flux paste is not smooth and the jetter is unable to print clean, crisp dots. For formulations with higher PSC content (e.g., Test 111), the appearance of filaments is observed. Pastes so formulated break up too slowly during printing and the droplets are no longer round. For this reason, a second associative thickener is added to the paste mixture, which increases the viscosity in the high shear range and provides improved shear recovery (e.g., Tests 112, 114).

[0053] Figure 2 shows the formation of a runner in the printing nozzle, clearly indicating the limit on the viscosity of the jet flux formulation. At 2000-3000 mPas it is possible to print without clogging, above 4000 clogging occurs. For example, tests 210 and 212 each illustrate printing of a jet flux formulation having a viscosity below 3000 mPas, but no clogging was observed, and tests 212 and 213 illustrate printing of a jet flux formulation having a viscosity above 4000 mPas, but clogging was observed.

[0054] Figure 3 shows the result of using a print paste that is too thin. Below 2000 mPas, the print paste is too thin (e.g., test 311) and the formation of spray mist is observed. In addition, the dispersant added in Example E increases the particle size, causing clogging of the injector nozzle.

[0055] FIG. 4 shows the printing results of various formulations of Jet Flux paste and illustrates the corresponding dot structures revealed during such testing.

[0056] III. Examples Preparation of flux paste formulation: The following flux paste formulation for jet valve dispensing is provided by first combining the micronized flux with the solvent as shown in the table below and mixing by a normal mixer or high-speed disperser after a defined production protocol. In the second step, the obtained material is first combined with the shear thinning agent and other additives. The final flux formulation is homogeneous and stable, with defined physical and chemical specifications, specifically, viscosity at 21°C, solids content, printability, and brazing performance. In addition, specific laboratory controls to confirm the viscosity reduction when shear effect is applied are also performed under constant temperature (21°C) and particle size defined by laser diffraction / scattering measurement.

[0057] [Table 1]

[0058] Preparation and testing of Examples A and B: In Examples A and B, diluted atomized flux pastes without rheological additives were investigated. The viscosity found is a result of the solids content. Thus, low viscosity is found at water contents of 25% and above. This paste exhibited good solderability, but printing was not possible. The viscosity increases at solids contents above 45%. For this formulation, the viscosity increases exponentially. The paste in Example B with 40% solids has a tendency to clog (i.e. the paste accumulates at the exit of the printer nozzle and the printed dots are no longer symmetrical). On vertical surfaces, the newly printed dots start to flow.

[0059] [Table 2]

[0060] [Table 3]

[0061] Preparation and testing of Example C: In another example (C), rheological additives and acrylate-based organic binders were added to the micronized flux paste from example B, after which a viscosity below 4000 mPas was measured in this composition, and the shear recovery increased from 83% to 94%. This directly affected the printability, and print tests of up to 45,000 dots could be printed without failure or interruption. In addition, the formation of printed dots was always symmetrical in both horizontal and vertical planes. In this configuration, the flux was accelerated almost completely out of the nozzle, and no material could be deposited (clogged) next to the nozzle.

[0062] [Table 4]

[0063] Preparation and testing of Example D: Tripling the organic binder in the flux formulation leads to a further reduction in viscosity from 3400 to 2000 mPas. Although printability remains high, the high hydrocarbon content leads to increased carbon black formation in the brazing angle test. The combustion of the organic components is no longer complete and black carbon precipitates on the solder seam, which is unacceptable to users. To reduce the viscosity of highly filled pastes, a different formulation is needed.

[0064] [Table 5]

[0065] Preparation and testing of Example E:

[0066] [Table 6]

[0067] Preparation and testing of Example F: As the following Example F illustrates, the addition of the dispersant effectively reduces the viscosity of the flux paste from just under 3000 mPas to 400 mPas. The solderability is excellent and practically no carbon black residue is found on the solder seam. Printability is given, but dropouts are observed in the continuous pressure test, which indicates that the nozzle should be cleaned. This can be seen by looking at the particle size of the flux mixture after the addition of this dispersant. Without addition, D50 values ​​in the range of 1 to 5 μm, preferably 3 μm, were measured. After the addition of the dispersant, the D50 increases to more than 90 μm and 95% of the particles are more than 200 μm. This means that the particles are already almost as large as the effective width of the injector nozzle, which usually has a diameter of 200 to 300 μm. When using this flux paste in jet printing, the injector is frequently clogged by too large particles or by weak agglomerates of the flux powder.

[0068] [Table 7]

[0069] The test of Example F shows two problems. First, if the viscosity is too low, the paste is not storage stable, since the flux settles and the solid phase separates during transportation or application. In addition, the printed dots are again asymmetrical and blend into one another. As already explained, the settling is prevented by using a structural thickener. However, to prevent the dots from blending into one another, it is better to use a second associative thickener that gives the paste a certain restoring force. This restoring force can be measured as shear recovery and is calculated from the ratio of the viscosities measured under high shear and at rest.

[0070] Preparation and testing of Example G: Example G illustrates the use of an associative thickener, again in conjunction with Jet Flux paste. The viscosity of the Jet Flux paste at 80% dilution increases from 2750 to 4200 mPas. At the same time, the shear recovery increases from 85 to 100%. The particle size does not change adversely, and the D95 remains below 10 μm. Printability is given and the formation of printed dots is symmetrical in vertical and horizontal orientation.

[0071] [Table 8]

[0072] Preparation and testing of Examples H and I: Examples H and I contain associative thickeners with increased viscosity, which has a positive effect on shear recovery, but the associated increase in viscosity leads to very severe clogging and a reduction in maximum print count of the flux dots.

[0073] [Table 9]

[0074] [Table 10]

[0075] Preparation and Testing of Example J

[0076] [Table 11]

[0077] Preparation and Testing of Example K

[0078] [Table 12]

[0079] Preparation and Testing of Example L

[0080] [Table 13]

[0081] IV: Printing performance of Jet Flux paste formulations

[0082] [Table 14]

[0083] [Table 15]

[0084] [Table 16]

[0085] V: Test results for Examples A to L: Flux formulations according to the formulations of Examples A-L above can be manufactured and filled into cartridges. The initial viscosity of each formulation was found to be 2000-4000 mPas, suitable for jetting and dispensing using a Nordson printhead. In this case, a long-term printing test was carried out for each formulation on a substrate area of ​​100x250 cm2, terminated after 180,000 points. Tables 16-18 as well as Figure 4 report / illustrate the results of the tests.

[0086] Specifically, Table 17 reports the number of dots printed, the viscosity (mPas) of the formulation, any observed blockage of the printer nozzle, and the overall performance of the resulting formulation. Table 18 reports the static viscosity (mPas) of the formulation, % shear recovery, average dot weight, and the overall performance of the printed formulation, where FIG. 4 supplementally illustrates the findings of Table 18, including depictions of each dot structure. Table 19 reports the particle size distribution (each PD5, PD50, and PD95) for each formulation, and the resulting print performance.

[0087] [Table 17]

[0088] [Table 18]

[0089] [Table 19]

[0090] As shown in Table 17, formulations with viscosities above 4000 mPas led to clogging of the nozzles of the print head, preventing the material from being completely ejected through the nozzles during printing. For example, each of the formulations of Examples B, H, I, J, and K exhibited at least some clogging behavior. Formulations with viscosities below 2000 mPas led to the formation and scattering of spray mist, such as the formulations of Examples D and F. In either case, the resulting residue at the exit of the print nozzle provides information about whether the paste is too thin (e.g., viscosity is too low, e.g., below 2000 mPas) or too thick (viscosity is too high, e.g., above 4000 mPas). For example, if the paste is too thick (i.e., viscosity is too high), paste threads may be observed to start growing in the nozzle, indicating a blockage of the nozzle. If the paste is too thin (e.g., viscosity is too low), fine deposits form on the substrate due to the resulting spray mist of the low-viscosity formulation. The printing process is stopped when: 1) the nozzle becomes clogged; 2) the paste residue dries out; and / or 3) agglomerates stick to the nozzle.

[0091] As shown in Table 18 and illustrated in Figure 4, high printing speeds and print quality were observed for the formulations of Examples C, D, G, and L. In these cases, the amount of flux per dot was controlled by the firing frequency under the printing conditions. The shear recovery of these formulations was found to be greater than 90%, which led to symmetrical and separated dots. In contrast, formulations B and F showed dots that overlapped and appeared as solid lines. This occurred due to the low elasticity of the paste, which led to the jet flux dots bursting and intermingling when the jet flux droplets hit the substrate surface. If the viscosity is too high and the recovery force is low, overlapping elongated droplets will form. All viscosities are measured by a Thermo Scientific Instruments Viscotester. Measurements were performed at 22°C, FL100, 11.5 / s.

[0092] As shown in Table 19, for some formulations, misfires and clogging of the nozzle occurred with increasing print time. This may suggest that agglomerates formed in the atomized paste, leading to nozzle clogging. In Example F, these agglomerates could be reliably detected using laser particle measurement. The cause was a dispersion additive, which at higher concentrations bridges the particles instead of keeping them spaced apart. This additive was also included in formulations E, J, and K, and its presence only led to very rare print failures. In Examples C, D, G, and L, high print speeds and print quality were observed, and these formulations contained well-dispersed flux particles, with 95% of the particles in solution below 10 μm.

[0093] The performance characteristics of the flux formulations of Examples A-L were tested, as presented in Table 20, and each formulation performed well in brazing experiments.

[0094] [Table 20]

[0095] As shown in Table 20, Formulations B, C, and L provided higher brazing seam quality as less carbon deposits appeared in the seam, the solidified solder was very uniform and smooth, and the gaps between the connecting parts were well filled, providing high joint strength.

[0096] Table 21 illustrates the overall performance of the jet flux formulations as a culmination of all of the tests performed for each of the previously described Tables 17-20, which results in the determination of the best performing formulation. However, it should be noted that while one formulation may exhibit the best test performance, different conditions and / or variations in the testing may result in different results. Thus, the best performing formulation determined should not be considered the only formulation exhibiting high performance, nor does it imply that other jet flux formations are also disadvantageous.

[0097] [Table 21]

[0098] The individual results have been assessed with a grade of 0 to 4 per category and a ranking has been formed in which, in terms of the best results, particularly good printing results are achieved with formulations C, D, G and L, as well as with viscosities between 2000 and 4200 mPas.

[0099] VI: Coating Examples: Example M In this example, the blended flux formulation of any one of Examples A-L is printed and brazed onto an aluminum sheet to achieve a heat exchanger component suitable for the construction of electric or hydrogen vehicle (HV) bodies, battery packs, and fuel cells.

[0100] Example N In this example, the blended flux formulation of any one of Examples A-L is printed and brazed onto an aluminum sheet to achieve heat exchanger parts suitable for construction of automobile or transportation climate control systems, such as condensers, gas coolers, evaporators, and heaters.

[0101] Example O In this example, the blended flux formulation of any one of Examples A-L is printed and brazed onto an aluminum sheet to achieve a heat exchanger part suitable for an automotive engine or powertrain as a radiator, oil cooler, fuel cooler, exhaust gas recirculation system (EGR), or charge air cooler.

[0102] Example P In this example, the blended flux formulation of any one of Examples A-L is printed and brazed onto an aluminum sheet to achieve a heat exchanger component suitable for cooling a photovoltaic device or solar collector.

[0103] Example Q In this example, the blended flux formulation of any one of Examples A-L is printed and brazed onto an aluminum sheet to achieve a heat exchanger part suitable for a component of a residential air conditioning system, such as a condenser, evaporator, reversible, or radiator.

[0104] Example R In this example, the blended flux formulation of any one of Examples A-L is printed and brazed onto an aluminum sheet to achieve a heat exchanger part suitable for refrigeration in industrial, domestic, commercial, and transportation applications, such as a condenser or evaporator for refrigerants or cooling fluids.

[0105] Aspects: Aspect 1 is a flux paste composition comprising one or more fluoroaluminate-based fluxing agents, one or more thickeners, a carrier, a dispersant, a wetting agent, a defoamer, a moderator, and a biocide.

[0106] Example 2 is the flux paste composition of Example 1, wherein the one or more fluoroaluminate based fluxing agents include both a KAlF4 fluxing agent and an AlCsF4 fluxing agent.

[0107] Example 3 is the flux paste composition of Example 2, wherein KAlF4 is present in a ratio of 19:3 to AlCsF4.

[0108] Aspect 4 is the flux paste composition of any one of Aspects 1-3, wherein the one or more fluoroaluminate based fluxing agents comprise 40% or more of the flux paste composition.

[0109] Aspect 5 is A flux paste composition according to any one of Aspects 1 to 4, wherein the one or more thickeners include any one of a cellulose ether-based thickener, a polysaccharide-based thickener, and / or an acrylate-based thickener.

[0110] Example 6 is the flux paste composition of any one of Examples 1-5, wherein the one or more thickeners is a polysaccharide thickener diutan gum, and the gum comprises 1% or less of the flux paste composition.

[0111] Example 7 is the flux paste composition of any one of Examples 1 to 6, wherein the carrier comprises water in an amount of 45% or more, based on the total weight of the flux paste composition.

[0112] Aspect 8 is the following condition: (i) the dispersant comprises a polymeric dispersant Disperbyk 190, the Disperbyk 190 comprising 2% or less of the flux paste composition; (ii) the wetting agent comprises ZetaSperse® 1600, the ZetaSperse® 1600 comprising 2% or less of the flux paste composition; (iii) the antifoaming agent comprises Surfynol 104, and the Surfynol 104 comprises 1% or less of the flux paste composition.

[0113] Aspect 9 is the flux paste composition of any one of Aspects 1-8, wherein the moderator comprises any one of polyethylene glycol PEG 400, polyethylene glycol PEG 1000, polyethylene glycol PEG 10000, polyethylene glycol PEG 2000, polypropylene glycol PPG 400, and / or polypropylene glycol PPG 2000, and the moderator comprises 1% or less of the flux paste composition.

[0114] Example 10 is the flux paste composition of any one of Examples 1-9, wherein the biocide comprises 2-phenoxyethanol, and the 2-phenoxyethanol comprises 1% or less of the flux paste composition.

[0115] Example 11 is a blended flux composition comprising a micronized flux paste comprising one or more fluoroaluminate fluxing agents and one or more rheology additives selected based on printing of the blended flux composition with a non-contact inkjet printing system.

[0116] Aspect 12 is a method for manufacturing a semiconductor device, comprising the steps of: (i) the one or more rheology additives comprise a polysaccharide shear thinning agent, the polysaccharide shear thinning agent comprising 5-10 wt. % of the blended flux composition; (ii) the one or more rheology additives include an acrylate-based binder, the acrylate-based binder comprising 3% to 12% by weight of the blended flux composition; (iii) the one or more rheological additives include a polyurethane-based thickener, and the polyurethane-based binder includes 2% by weight to 5% by weight of the blended flux composition; (iv) the one or more rheological additives comprise a polymeric dispersant, and the polymeric dispersant comprises 2 wt% to 5 wt% of the flux paste composition.

[0117] Example 13 is the blended flux composition of Example 11 or Example 12, further comprising an aqueous carrier, the aqueous carrier comprising 5 wt% to 70 wt% of the flux paste composition.

[0118] Example 14 is a method of printing a flux formulation comprising inkjet printing a blended flux formulation prepared from a micronized flux concentrate, the micronized flux concentrate comprising one or more fluoroaluminate fluxing agents, one or more thickeners, a carrier, a dispersant, a wetting agent, a defoamer, a moderator, and a biocide.

[0119] Example 15 is the method of example 14, wherein the micronized flux concentrate has an average particle size diameter of 100 μm to 1 μm as determined by laser diffraction based on Mie scattering.

[0120] Example 16 is the method of example 14 or example 15, wherein the micronization of the flux concentrate is performed by a jet mill process.

[0121] Example 17 is the method of any one of Examples 14-16, wherein the micronized flux concentrate is milled to a particle size of about 1 μm to 30 μm.

[0122] Example 18 is the method of any one of Examples 14 to 17, wherein the viscosity of the micronized flux paste is about 500 mPas to 12,000 mPas.

[0123] Example 19 is the method of any one of Examples 14 to 18, wherein the viscosity of the blended flux formulation is about 1,000 mPas to 4,8,000 mPas.

[0124] Aspect 20 is directed to inkjet printing using the following techniques: (i) non-contact technology; (ii) Drop-on-demand inkjet process technology; (iii) a technique with a printing nozzle having a diameter of 0.3 mm to 1.2 mm; (iv) a technique with a droplet printing frequency of 250 Hz or more.

[0125] Example 21 is the method of any one of Examples 14-20, wherein the blended flux formulation is inkjet printed at a speed greater than 150 m / min.

[0126] Example 22 is the method of any one of Examples 14-21, wherein the blended flux formulation is printed and brazed onto aluminum sheets to achieve heat exchanger parts, or parts that enable the construction of electric EV or hydrogen vehicle (HV) bodies, battery packs, fuel cells.

[0127] Example 23 is the method of any one of Examples 14-22, wherein the blended flux formulation is printed and brazed onto an aluminum sheet to achieve a heat exchanger part or a part used in an automotive or transportation environmental control system as a condenser, gas cooler, evaporator, or heater.

[0128] Example 24 is the method of any one of Examples 14-23, wherein the blended flux formulation is printed and brazed onto an aluminum sheet to achieve a heat exchanger part or a part used in an automobile engine or powertrain as a radiator, oil cooler, fuel cooler, exhaust gas recirculation (EGR) system, or charge air cooler (CAC).

[0129] Example 25 is the method of any one of Examples 14-24, wherein the blended flux formulation is printed and brazed onto an aluminum sheet to achieve heat exchanger parts and parts used for cooling photovoltaic elements or solar collectors.

[0130] Example 26 is the method of any one of Examples 14-25, wherein the blended flux formulation is printed and brazed onto an aluminum sheet to achieve a heat exchanger part used in residential air conditioning as a condenser, evaporator, reversible, or radiator.

[0131] Example 27 is the method of any one of Examples 14-26, wherein the blended flux formulation is printed and brazed onto an aluminum sheet to achieve heat exchanger parts used in refrigeration and cooling in industrial, domestic, commercial, and transportation areas as condensers or evaporators for refrigerants or cooling fluids.

Claims

1. 1. A flux paste composition comprising: one or more fluoroaluminate-based fluxing agents; One or more thickening agents; A carrier; A dispersant; A wetting agent; A defoaming agent; A moderator and and a biocide.

2. The one or more fluoroaluminate-based fluxing agents are KAlF 4 Fluxing agent and AlCsF 4 2. The flux paste composition of claim 1, comprising both a fluxing agent and a fluxing agent.

3. The KAlF 4 However, the AlCsF 4 3. The flux paste composition of claim 2, wherein the flux paste composition is present in a ratio of 19:3 to 19:

3.

4. 10. The flux paste composition of claim 1, wherein the one or more fluoroaluminate based fluxing agents comprise 40% or more of the flux paste composition.

5. 2. The flux paste composition of claim 1, wherein the one or more thickeners are selected from the group consisting of cellulose ether thickeners, polysaccharide thickeners, and acrylate thickeners.

6. 6. The flux paste composition of claim 5, wherein said one or more thickeners is a polysaccharide thickener diutan gum, said gum comprising 1% or less of said flux paste composition.

7. 2. The flux paste composition of claim 1, wherein the carrier comprises water in an amount of 45% or more, based on the total weight of the flux paste composition.

8. The following conditions: (i) the dispersant comprises a polymeric dispersant Disperbyk 190, the Disperbyk 190 comprising 2% or less of the flux paste composition; (ii) the wetting agent comprises ZetaSperse® 1600, the ZetaSperse® 1600 comprising 2% or less of the flux paste composition; 2. The flux paste composition of claim 1, wherein at least one of the following is present: (iii) the antifoaming agent comprises Surfynol 104, and the Surfynol 104 comprises 1% or less of the flux paste composition.

9. 2. The flux paste composition of claim 1, wherein the moderator is selected from the group consisting of polyethylene glycol PEG 400, polyethylene glycol PEG 1000, polyethylene glycol PEG 10000, polyethylene glycol PEG 2000, polypropylene glycol PPG 400, and polypropylene glycol PPG 2000, and wherein the moderator comprises 1% or less of the flux paste composition.

10. 2. The flux paste composition of claim 1, wherein the biocide comprises 2-phenoxyethanol, and wherein the 2-phenoxyethanol comprises 1% or less of the flux paste composition.

11. 1. A method for printing a flux composition, comprising: inkjet printing a blended flux formulation prepared from a micronized flux concentrate, said micronized flux concentrate comprising: one or more fluoroaluminate fluxing agents; One or more thickening agents; A carrier; A dispersant; A wetting agent; A defoaming agent; A moderator and a biocide.

12. 12. The method of claim 11, wherein the viscosity of the blended flux formulation is from about 1,000 mPas to 4,8,000 mPas.

13. The inkjet printing is carried out by the following techniques: (i) non-contact technology; (ii) Drop-on-demand inkjet processing technology; (iii) Techniques with printing nozzles having a diameter between 0.3 mm and 1.2 mm; (iv) a droplet printing frequency of 250 Hz or greater.

14. 12. The method of claim 11, wherein the blended flux formulation is inkjet printed at a speed greater than 150 m / min.

15. 12. The method of claim 11, wherein the blended flux formulation is printed and brazed onto an aluminum sheet to achieve a mechanical part selected from the group consisting of a car body, a battery pack, a fuel cell, a condenser, a gas cooler, an evaporator, a heater, a radiator, an oil cooler, a fuel cooler, an exhaust gas recirculation system, a charge air cooler, a heat exchanger for a photovoltaic device, a heat exchanger for a solar thermal collector, and an evaporator.

Citation Information

Cited By

  • Low-viscosity flux composition usable for printing using digital inkjet head

    JP2025181700A